Long-term outcomes after transcatheter aortic valve implantation in failed bioprosthetic valves. (27th June 2020) - Bleiziffer, Sabine; Simonato, Matheus; Webb, John G; Rodés-Cabau, Josep; Pibarot, Philippe; Kornowski, Ran; Windecker, Stephan; Erlebach, Magdalena; Duncan, Alison; Seiffert, Moritz; Unbehaun, Axel; Frerker, Christian; et al.
Abstract: Aims: Due to bioprosthetic valve degeneration, aortic valve-in-valve (ViV) procedures are increasingly performed. There are no data on long-term outcomes after aortic ViV. Our aim was to perform a large-scale assessment of long-term survival and reintervention after aortic ViV. Methods and results: A total of 1006 aortic ViV procedures performed more than 5 years ago [mean age 77.7 ± 9.7 years; 58.8% male; median STS-PROM score 7.3% (4.2–12.0)] were included in the analysis. Patients were treated with Medtronic self-expandable valves (CoreValve/Evolut, Medtronic Inc., Minneapolis, MN, USA) ( n  = 523, 52.0%), Edwards balloon-expandable valves (EBEV, SAPIEN/SAPIEN XT/SAPIEN 3, Edwards Lifesciences, Irvine, CA, USA) ( n  = 435, 43.2%), and other devices ( n  = 48, 4.8%). Survival was lower at 8 years in patients with small-failed bioprostheses [internal diameter (ID) ≤ 20 mm] compared with those with large-failed bioprostheses (ID > 20 mm) (33.2% vs. 40.5%, P  = 0.01). Independent correlates for mortality included smaller-failed bioprosthetic valves [hazard ratio (HR) 1.07 (95% confidence interval (CI) 1.02–1.13)], age [HR 1.21 (95% CI 1.01–1.45)], and non-transfemoral access [HR 1.43 (95% CI 1.11–1.84)]. There were 40 reinterventions after ViV. Independent correlates for all-cause reintervention included pre-existing severe prosthesis–patient mismatch [subhazard ratio (SHR) 4.34 (95% CI 1.31–14.39)], device malposition [SHR 3.75 (95% CI 1.36–10.35)], EBEV [SHR 3.34 (95% CI 1.26–8.85)], and age [SHR 0.59 (95% CI 0.44–0.78)]. Conclusions: The size of the original failed valve may influence long-term mortality, and the type of the transcatheter valve may influence the need for reintervention after aortic ViV. Graphical Abstract: